2022
DOI: 10.1177/23326492221078304
|View full text |Cite
|
Sign up to set email alerts
|

Assessing and Extending Colorblind Racism Theory Using National Survey Data

Abstract: Eduardo Bonilla-Silva’s work on colorblind racism has become a prominent theoretical framework for analyzing racial attitudes, ideologies, and discourses in the contemporary United States. However, the scholarship has yet to produce an empirically rigorous, quantitative assessment of colorblind racism to document the theory’s generalizability and assess it as a theory of racial attitudes. In this article, we build upon the rich body of qualitative research to develop a novel measurement model of colorblind rac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 53 publications
1
0
0
Order By: Relevance
“…These results echo earlier work examining the developmental processes of White people's attitudes about race, which shows that an awareness of structural/systemic forms of racism, and acknowledgement of White privilege, often precede commitments to engaging in antiracist actions (D'Andrea & Daniels, 1999;Derman-Sparks & Phillips, 1997). They are also supported in more recent research, which finds that awareness of structural racism mediates the relationship between colorblind racism and support for affirmative action policies (Hamilton et al, 2022). In a recent meta-analysis on CBRI in psychology, Yi et al (2023) found that the denial and minimization of race and racism (i.e., CBRI) was negatively associated with a host of variables that are antithetical to racial justice.…”
Section: Psychological Connections Among Antiracism White Privilege A...supporting
confidence: 83%
“…These results echo earlier work examining the developmental processes of White people's attitudes about race, which shows that an awareness of structural/systemic forms of racism, and acknowledgement of White privilege, often precede commitments to engaging in antiracist actions (D'Andrea & Daniels, 1999;Derman-Sparks & Phillips, 1997). They are also supported in more recent research, which finds that awareness of structural racism mediates the relationship between colorblind racism and support for affirmative action policies (Hamilton et al, 2022). In a recent meta-analysis on CBRI in psychology, Yi et al (2023) found that the denial and minimization of race and racism (i.e., CBRI) was negatively associated with a host of variables that are antithetical to racial justice.…”
Section: Psychological Connections Among Antiracism White Privilege A...supporting
confidence: 83%